BUSINESS STRATEGIES AND NEW MODELS OF WOMEN'S ENTREPRENEURSHIP IN THE DIGITAL ECONOMY - Y. A. Semenova (Дискурс, 2018)
The article considers primary areas of research of female entrepreneurship by Russian scientists. Business strategies and new models of women's entrepreneurship in modern Russia are analyzed. The results of the study of Women's Business Index (WBI) are presented. Distinctive features of women's entrepreneurship are presented. The study estimates the prospects of female business in the conditions of digital economy. At the basis of the new models of women's entrepreneurship lies the interaction of producers and end-users without intermediaries that engages high technologies to obtain maximum effect. The article specifies the most effective ways of promoting the women's initiative to develop their own businesses as an essential component of the modern labor market.